Clinical outcomes of pediatric patients receiving multimodality treatment of second central nervous system relapse of neuroblastoma. Issue 2 (9th November 2022) - Tringale, Kathryn R.; Wolden, Suzanne L.; Casey, Dana L.; Kushner, Brian H.; Luo, Leo; Pandit‐Taskar, Neeta; Souweidane, Mark; Cheung, Nai‐Kong V.; Modak, Shakeel; Basu, Ellen M.; Kramer, Kim
Abstract: Background: In high‐risk neuroblastoma, multimodality therapy including craniospinal irradiation (CSI) is effective for central nervous system (CNS) relapse. Management of post‐CSI CNS relapse is not clearly defined. Procedure: Pediatric patients with neuroblastoma treated with CSI between 2000 and 2019 were identified. Treatment of initial CNS disease (e.g., CSI, intraventricular compartmental radioimmunotherapy [cRIT] with 131 I‐monoclonal antibodies targeting GD2 or B7H3) and management of post‐CSI CNS relapse ("second CNS relapse") were characterized. Cox proportional hazards models to evaluate factors associated with third CNS relapse and overall survival (OS) were used. Results: Of 128 patients (65% male, median age 4 years), 19 (15%) received CSI with protons and 115 (90%) had a boost. Most (103, 81%) received cRIT, associated with improved OS (hazard ratio [HR] 0.3, 95% confidence interval [CI]: 0.1–0.5, p < .001). Forty (31%) developed a second CNS relapse, associated with worse OS (1‐year OS 32.5%, 95% CI: 19‐47; HR 3.8; 95% CI: 2.4–6.0, p < .001), and more likely if the leptomeninges were initially involved (HR 2.5, 95% CI: 1.3–4.9, p = .006). Median time to second CNS relapse was 6.8 months and 51% occurred outside the CSI boost field. Twenty‐five (63%) patients underwent reirradiation, most peri‐operatively (18, 45%) with focal hypofractionation. Eight (20%) patients with second CNS relapse received cRIT, associated with improved OS (HR 0.1; 95% CI: 0.1–0.4, p < .001). Conclusions: CNS relapse after CSI for neuroblastoma portends a poor prognosis. Surgery with hypofractionated radiotherapy was the most common treatment. Acknowledging the potential for selection bias, receipt of cRIT both at first and second CNS relapse was associated with improved survival. This finding necessitates further investigation.